2022
DOI: 10.1155/2022/5582811
|View full text |Cite
|
Sign up to set email alerts
|

A Substance P (SP)/Neurokinin-1 Receptor Axis Promotes Perineural Invasion of Pancreatic Cancer and Is Affected by lncRNA LOC389641

Abstract: Perineural invasion (PNI) is considered to be a main reason for the poor prognosis of pancreatic cancer. In the present study, we analyzed the roles of substance P (SP)/neurokinin-1 receptor (NK-1R) and lncRNA LOC389641 in pancreatic cancer PNI. Pancreatic cancer cell lines BxPC-3 and MIAPaCa-2 were cocultured with SH-SY5Y cells and then stimulated with SP to simulate the in vivo influence of ganglia on pancreatic cancer. The BxPC-3 and MIAPaCa-2 cells were transfected with a neurokinin-1 receptor (NK-1R) over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…These results suggest that lncRNA LOC389641 may promote EMT in PTC, associated with tumor progression. In addition to PTC, research also suggests that LOC389641 can influence the progression of pancreatic cancer and lung adenocarcinoma through other pathways [ 112 , 113 ].…”
Section: Lncrnas Impact Ptc Progression Via Emt Pathwaysmentioning
confidence: 99%
“…These results suggest that lncRNA LOC389641 may promote EMT in PTC, associated with tumor progression. In addition to PTC, research also suggests that LOC389641 can influence the progression of pancreatic cancer and lung adenocarcinoma through other pathways [ 112 , 113 ].…”
Section: Lncrnas Impact Ptc Progression Via Emt Pathwaysmentioning
confidence: 99%
“…Peripheral nerves are essential in controlling the tumor microenvironment by activating tumor cells and promoting invasion and metastasis [143]. SP, via NK-1R, promoted perineural invasion in pancreatic cancer; this invasion was associated with a poor prognosis and inhibited by the SF10A (TNFRSF10A)/NF-κB pathway mediated by LOC389641 [151].…”
Section: Neurokinin-1 Receptor and Nerve Terminalsmentioning
confidence: 99%
“…Gil et al Am J Cancer Res 2024;14(2):448-466 showed that glial cell-derived neurotrophic factor enhanced pancreatic cancer invasion via RET activation in a paracrine-dependent manner [13]. Recently, the substance P/neurokinin 1 receptor signaling axis has been shown to promote PDAC metastasis [14]. However, these studies did not address the importance of neuronal factors in PDAC prognosis.…”
Section: Introductionmentioning
confidence: 99%